2008
DOI: 10.1111/j.1365-2966.2007.12683.x
|View full text |Cite
|
Sign up to set email alerts
|

The hydrogen-deficient knot of the ‘born-again’ planetary nebula Abell 58 (V605 Aql)

Abstract: We have analysed deep optical spectra of the ‘born‐again’ planetary nebula Abell 58 and its hydrogen‐deficient knot, surrounding V605 Aql, which underwent a nova‐like eruption in 1919. Our analysis shows that the extinction towards the central knot is much higher than previously thought, with c(Hβ) = 2.0. The outer nebula is less reddened, with c(Hβ) = 1.04. We find that the outer nebula has a Ne/O ratio higher than the average PN value. The electron temperature we derive for the central knot varies widely dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 40 publications
3
83
3
Order By: Relevance
“…Perhaps a stronger link to binarity is the high adf, where recent work has shown that the PNe with the highest known adfs all host a central binary star (Corradi et al 2015, Jones et al in prep;and references therein). High adfs also strengthen the link between PNe with binary central stars and other binary phenomena, such as novae, which are also known to display extremely high adfs (Wesson et al 2003(Wesson et al , 2008. We strongly encourage the detailed study of other post-CE CSPN and their host nebulae (as well as the continued search for new systems) in order to improve the statistics and to establish the parameter space for future modelling and study of the CE and its effect on PN formation and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps a stronger link to binarity is the high adf, where recent work has shown that the PNe with the highest known adfs all host a central binary star (Corradi et al 2015, Jones et al in prep;and references therein). High adfs also strengthen the link between PNe with binary central stars and other binary phenomena, such as novae, which are also known to display extremely high adfs (Wesson et al 2003(Wesson et al , 2008. We strongly encourage the detailed study of other post-CE CSPN and their host nebulae (as well as the continued search for new systems) in order to improve the statistics and to establish the parameter space for future modelling and study of the CE and its effect on PN formation and evolution.…”
Section: Discussionmentioning
confidence: 99%
“…There are several cases of this type of explosive-like, late events in PNe, especially associated to the late helium-shell flash associated to the bornagain class of PNe Wesson et al 2008) or to oxygen-neon-magnesium nova-like events suggested for the born-again PN A 58 (Lau et al 2011) or for BD+30…”
Section: Discussionmentioning
confidence: 99%
“…Wesson (2008a) found a C/O ratio of less than unity and substantial quantities of neon in the ejecta of both Abell 30 and Abell 58, which are not predicted by very late thermal pulse models. The ejecta abundances are more akin to that seen in neon-rich novae!…”
Section: (B)mentioning
confidence: 99%